A new fuzzy version of euler’s method for solving differential equations with fuzzy initial values - Muhammad Zaini Ahmad,; Mohammad Khatim Hasan, (Universiti Kebangsaan Malaysia, 2011)
This paper proposes a new fuzzy version of Euler’s method for solving differential equations with fuzzy initial values. Our proposed method is based on Zadeh’s extension principle for the reformulation of the classical Euler’s method, which takes into account the dependency problem that arises in fuzzy setting. This problem is often neglected in numerical methods found in the literature for solving differential equations with fuzzy initial values. Several examples are provided to show the advantage of our proposed method compared to the conventional fuzzy version of Euler’s method proposed in the literature.